Differential induction, purification and characterization of cold active lipase from Yarrowia lipolytica NCIM 3639 - Yadav, K. N. Sathish; Adsul, Mukund G.; Bastawade, Kulbhushan B.; Jadhav, D. D.; Thulasiram, H. V.; Gokhale, D. V. (Bioresource Technology, 2011)
The production, purification and characterization of cold active lipases by Yarrowia lipolytica NCIM 3639 is described. The study presents a new finding of production of cell bound and extracellular lipase activities depending upon the substrate used for growth. The strain produced cell bound and extracellular lipase activity when grown on olive oil and Tween 80, respectively. The organism grew profusely at 20 degrees C and at initial pH of 5.5, producing maximum extracellular lipase. The purified lipase has a molecular mass of 400 kDa having 20 subunits forming a multimeric native protein. Further the enzyme displayed an optimum pH of 5.0 and optimum temperature of 25 degrees C. Peptide mass finger printing reveled that some peptides showed homologues sequence (42%) to Yarrowia lipolytica LIP8p. The studies on hydrolysis of racemic lavandulyl acetate revealed that extracellular and cell bound lipases show preference over the opposite antipodes of irregular monoterpene, lavandulyl acetate. (C) 2011 Elsevier Ltd. All rights reserved.
Keywords: Cell bound lipase; Cold active lipase; Extracellular lipase; Lavandulyl acetate; Oligomeric lipase